Social network dynamics in international students’ learning - Taha, Nashrawan; Cox, Andrew (Proceedings of the International Conference on Networked Learning, 2010)
The potential for the internationalisation of UK HE to bring diverse viewpoints and perspectives into the curriculum has not been fully realised. One of the many obstacles to this may be our lack of understanding of how international students use and build social networks for learning, information sharing and support, and how this impacts on engagement and learning. The literature suggests various ways in which network positions and learning might be associated. In this study we used a range of tools including social network analysis (SNA), observation, interviews and photographic evidence to investigate the social networks developing in a class with a very diverse make up. We wanted to discover how the network develops and what shapes this. We found that the network shape was less immediately visible than might have been anticipated. Programme of study and language were found to have a strong effect on who talked to whom. In class networks were strongly influenced by the timing and character of the assessment, but pre-existing ties outside the classroom were significant for on-going affective support. Isolation in the network tended to be linked to where the person lived and cultural factors. Based on these findings we develop a detailed plan for a curriculum redesign. We propose a more intense and complex form of group work. The topic and approach of the assignment would stress a multi-cultural approach and group make up would be determined by the tutor, based primarily on mixing nationalities. We also propose that students share their products online with wider communities, in some part bringing their external networks into play and visibility in the classroom, certainly giving centrality to network related skills as a classroom issue. In addition, we propose using a social bookmarking tool to minimise isolation of some individuals in the network. Future work will be to implement and evaluate these interventions.